ChemInform Abstract: A Novel Route for the Synthesis of 3‐(Pyrrol‐1‐yl)‐indolin‐2‐ones. Issue 12 (14th March 2013) - Sarkar, Swarbhanu; Saha, Bidula; Naskar, Subhendu
Abstract A high‐yielding environmentally benign protocol for the synthesis of title compounds (III) using a Lewis acid surfactant catalyst which is crucial for a successful transformation.